Diatom-mimetic channeled mesoporous silica membranes: self-organized formation of a hierarchical porous framework. (19th November 2020) - Kitamura, Riku; Watanabe, Hiroto; Somekawa, Shouichi; Ono, Yuto; Owari, Yuka; Oaki, Yuya; Imai, Hiroaki
Abstract : Silica membranes having macrochannels with mesoporous walls were spontaneously fabricated using a self-organized process with rapid gelation of concentrated silicate and surfactant precursor solutions. Abstract : Silica membranes having macrochannels with mesoporous walls were spontaneously fabricated using a self-organized process with rapid gelation of concentrated silicate and surfactant precursor solutions. The specific hierarchical porous framework consisting of straight macrochannels ca. 1 μm in diameter is similar to that of a biological silica frustule of diatoms. We applied the diatom-mimetic channeled mesoporous silica membranes to high-permeability-rate filtration and enhanced photocatalytic systems. The presence of macrochannels was found to improve the performance of the mesoporous silica membranes in filtration and as a photocatalyst carrier.